Using virtual classroom for teaching special needs students in inclusive classrooms during and beyond COVID-19: Teachers’ perspectives - Alhwaiti, Mohammed (Anales de Psicología / Annals of Psychology, 2024)
Encouraging and continuing inclusive learning environments is important to allow all students to be able to fully participate, engage, and learn. The online learning environment obliges educators to think creatively about how to achieve this goal. The aim was to investigate using virtual classroom for teaching special needs students in inclusive classrooms during and beyond Covid-19 from the perspectives of their teachers. Teachers of special education from integration schools in the middle stage in Makkah were targeted. A 15- item survey instrument was developed particularly for this research study . Quantitative research is carried out with the aim to investigate using virtual classroom(VC) for teaching special needs students in inclusive classrooms during and beyond Covid-19 from the perspectives of their teachers. A survey method was used. Data were collected through a structured self-administered questionnaire, which was based on the technology acceptance model(TAM). Pearson correlation(R) and multiple regression (MRA) were used to analyze data . Results indicated that the BI is positively affected by PU, PEOU. PU, PEOU yielded a coefficient of multiple regression (R) and a multiple correlation square. This shows that a total variance in BI is accounted for by PU, PEOU. In conclusion, the findings in this study contribute to the literature on TAM and its use in special education in particular.